DEIKSIS DALAM BAHASA INGGRIS DAN BAHASA BANGGAI (SUATU ANALISIS KONTRASTIF) - Kasebae, Nurfadlia Mukhlis Pente (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2013)
Deixis forms in English and Banggai language are very important in every communication to avoid misunderstanding between speaker and hearer. These forms can be found in human conversation.   This study is an attempt to identify, classify, analyze, and contrast the deixis in English and Banggai language. The research questions must be answered are : What are the kinds of deixis in English and Banggai language and what are the similarities and differences in both of the languages. To solve those problems, the writer uses the concepts of Lavinson and Lado. In terms of collecting data, the English data have been taken from some English books and Banggai data have been collected by interviewing the native speakers of Banggai language who live in Palam village in Banggai Kepulauan district. In makes this investigation, the writer uses the descriptive method based on  Levinson?s  and Lado?s theory. The result of this research shows that deixis in English and Banggai language have some similarities and differences, those are form, function, distribution and types. In terms of similarity those two  languages have function and distribution, and in terms of differences are form and types. The writer expects that this study can help students and readers to learn pragmatics aspects that is deixis. The writer realizes that this research is far from being complete.   Key Words : The Form of Deixis, English and Banggai Language, Contrastive Analysis